Forensic accounting: φraud examination and prevention through the identification of fraudster’s profile and organizational culture - Παπαχρήστου, Γεώργιος (2021)
Fraud is a multidimensional issue that concerns investors, regulators, auditors, and the public. The wave of corporate failures at the beginning of the 21st century, raised interest on this issue, making forensic accounting an emerging and promising mechanism available to professionals for effective and efficient prevention, detection, and deterrence of fraud and also a challenging research area for academics. Even though regulation was issued in the aftermath of fraud scandals and the disclosure of corporate governance deficiencies, still legislating human behavior is impossible. As it is “human beings who commit fraud” (Ramamoorti, 2008), it is important to reveal the inner forces that lead employees to fraudulent acts, and in turn delve into their psychology. However, considering that employees work within a context, their behavior affects the firm and vice-versa, firm’s organizational culture does affect their behavior. That being the case, the objective of this thesis is to map the profile of a possible fraud perpetrator and, in turn answer the question of “why employees do bad things”. To achieve this aim, a sample of 214 employees working in private firms in Greece was examined through a four-stage research. In the first stage of the research, the impact of personal attributes, involving personality traits and demographics, on employees’ propensity to commit or engage in fraud, is being explored. The results reveal that an employee who is characterized as being unconscientious, disagreeable, close to experience, and extrovert, includes the typical characteristics of a possible fraud perpetrator. Then, in the second stage of the research, the impact of organizational culture on employees’ fraudulent behavior is being examined. The results reveal that the existence of an ethical organizational culture within a firm reduces fraud likelihood. In specific, congruency of management, feasibility, and transparency, significantly influence employees’ aversion to fraud. In the third stage of the research the moderating role of organizational culture on the relationship between personal attributes and fraudulent behavior is being explored. The results reveal a significant intervening role of ethical culture on the relationships between openness and extraversion with behavior. Finally, in the fourth stage of the research, four additional analyses are being performed. The first examines the impact of personal attributes and organizational culture simultaneously on employees’ fraudulent behavior. The other three analyses investigate the personal attributes that affect an employee’s tendency to commit financial statement fraud, be corrupted, and misappropriate firm’s assets. The results reveal that when culture is included in the research model, only conscientiousness and openness affect an employee’s behavior. In addition, regarding the fraudster’s profile in view of the three types of occupational fraud, the possible financial statement fraud perpetrator and the employee who is likely to commit asset misappropriation, is unconscientious and close to experience, whistle the possible corrupted employee is extravert. The results of this thesis are useful to academics and professionals. In terms of academic contribution, this thesis expands the forensic accounting literature on the behavioral analysis of fraud by mapping the profile of a possible fraud perpetrator and applying an interdisciplinary approach through the use of accounting and psychology theories. In terms of professionals, the results of the thesis can be used during selection and recruiting processes, as an additional means of evaluating employees’ tendency to fraud, preventing in this way future fraud incidents within the firm. In addition, the results can be used as red flags by auditors and forensic accountants when investigating a fraud case.